Impact of Tourist Attractions on Word of Mouth: A Case Study of Fort Marlborough, Bengkulu - Hariani Tarigan; Rindika Pramadanti; Aris Budiono (Goodwood Publishing, 2025)
Purpose: This study aims to determine the influence of tourist attractions on word-of-mouth (WOM), specifically in terms of the decision to visit and visitor satisfaction at Fort Marlborough. Research Methodology: This research employs a quantitative method, with data collection conducted in May 2025 at Fort Marlborough in Bengkulu Province. The respondents were visitors to Fort Marlborough, with a sample size of 130 people selected using accidental sampling techniques. A Likert scale was used as the primary measurement tool. Path Analysis was applied to evaluate the proposed hypothesis, allowing for the assessment of both direct and indirect relationships. This analysis was performed using SmartPLS 3 software. Results: Direct influence, tourist attraction affects the three bound variables, namely, the decision to visit, visitor satisfaction, and word of mouth. In terms of indirect influences, tourist attractions affect word of mouth through the decision to visit and the satisfaction of visitors to Fort Marlborough. Conclusions: This study shows that tourist attractions significantly influence visiting decisions, satisfaction, and word-of-mouth at Fort Marlborough. It highlights the mediating roles of visit decisions and satisfaction, offering insights for destination managers to enhance attraction quality and visitor experience. Limitations: This study is limited to a single historical destination (Fort Marlborough) with a small sample size (130 respondents) and a cross-sectional design, which may limit generalizability. In addition, only four variables were examined, excluding other potential factors. Contributions: This study contributes to the tourism and marketing disciplines by empirically demonstrating how tourist attractions influence word of mouth through visiting decisions and visitor satisfaction in the context of historical tourism in Indonesia. Practically, the findings provide guidance for heritage destination managers and local governments to enhance the visitor experience and strengthen word-of-mouth promotion.